Implementation of Sophisticated Controlling System in a Company (Case of Gearspect Group s.r.o.) - Horáčková, Jana; Malý, Milan, 1936-; Kubíček, Aleš; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2014)
The aim of the thesis is the implementation of a Controlling System in Gearspect Group s.r.o. company, and its results and contributions to the management of the company. Main contribution of author will be practical application of Controlling Information Systems and generalization of the results for Controlling System Implementation in small-medium sized companies within Czech engineering industry. The central goal of this thesis is to pinpoint the necessity and significance of the successful application of controlling and its instruments in management of a company. This thesis includes the theoretical framework of controlling, literature overview of controlling applied, analysis of current situation and processes in the company, suggesting the optimum implementation of such system, and finally the results in the company that can be further generalized for small-medium sized companies within the Czech engineering industry.
Vedoucí práce: Milan Malý
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses